Exploiting Seasonal Varieties of Tomato Cultivation for Enhanced Yield and Nutritional Impact in Uzbekistan: Memanfaatkan Varietas Musiman Budidaya Tomat untuk Meningkatkan Hasil dan Dampak Gizi di Uzbekistan - Xayitovna, Pirimqulova Muxabbat; Faxriddinovich, Mamarajabov Samandarbek; Avazbek qizi, Abduvahobova Mohinurxon; Yunus qizi, Xolmatova Marjona (Universitas Muhammadiyah Sidoarjo, 2023)
This comprehensive study investigates the varied seasonal tomato cultivars of Uzbekistan, characterizing their cultivation practices and vegetative periods. Given tomatoes' notable dietary value, a detailed examination of more than 1,000 different varieties was conducted, drawing attention to their growth in both open and protected environments. Leveraging global agricultural data, with a specific focus on leading tomato producers like China, USA, India, Turkey, and Egypt, we've honed in on the cultivation practices in Uzbekistan, where tomatoes comprise a significant 40-45% of total vegetable crops. Our results indicate that in 2010, tomatoes were cultivated on 75,000 hectares in Uzbekistan with a distribution pattern indicating 70% for processing, 10-15% for local market sale, and 15-20% for export. These findings offer the potential to boost both the local economy and the nutritional intake of the population, underlining the importance of tomatoes as a key dietary staple with implications for broader agricultural policy, particularly in areas focused on health and economic development.Highlights: Uzbekistan dedicates 40-45% of its total vegetable crop area to tomato cultivation, reflecting its substantial dietary and economic value. Diverse tomato varieties, suited to both open and protected growth, are integral to achieving high yield and ensuring local to global supply chains. The distribution of tomato produce in Uzbekistan offers potential for economic growth and improved local nutritional intake, with 70% processed, 10-15% sold locally, and 15-20% exported. Keywords: Tomato Cultivation, Seasonal Varieties, Uzbekistan Agriculture, Dietary Impact, Global Tomato Production